2005
DOI: 10.1080/09297040590911202
|View full text |Cite
|
Sign up to set email alerts
|

Memory and Learning in Children with 22q11.2 Deletion Syndrome: Evidence for Ventral and Dorsal Stream Disruption?

Abstract: This study examined memory functioning in children and adolescents with 22q11.2 Deletion Syndrome (DS; velocardiofacial syndrome). An overall verbal better than nonverbal memory pattern was evident on the Test of Memory and Learning (TOMAL), with children with 22q11.2 DS performing significantly below their siblings and children with low average IQ but similar to children with autism on facial memory. Children with 22q11 DS also performed significantly below their siblings on tests of verbal working memory. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 40 publications
9
40
0
Order By: Relevance
“…These regions are respectively part of the "where" dorsal pathway, responsible for object spatial localization (Creem & Proffitt, 2001), and the "what" ventral stream that sustains object and face recognition (Creem & Proffitt, 2001). Both pathways are thought to be impaired in patients with the microdeletion as deficits in visuo-spatial skills (Antshel et al, 2008), face recognition (Andersson et al, 2008;Lajiness-O'Neill et al, 2005) and social skills (Baker & Vorstman, 2012;Baker & Skuse, 2005) have been consistently described in 22q11DS. Furthermore, functional connectivity alterations of high-level visual networks had already been identified in our former ICA study , and abnormal white matter structure in parietal regions have been described in DTI studies including both with increased (da Silva Alves et al, 2011;Simon et al, 2005Simon et al, , 2008 and decreased (Barnea-Goraly et al, 2003Sundram et al, 2010) fractional anisotropy.…”
Section: Reorganization Of Modular Communities In Patients With 22q11dsmentioning
confidence: 95%
“…These regions are respectively part of the "where" dorsal pathway, responsible for object spatial localization (Creem & Proffitt, 2001), and the "what" ventral stream that sustains object and face recognition (Creem & Proffitt, 2001). Both pathways are thought to be impaired in patients with the microdeletion as deficits in visuo-spatial skills (Antshel et al, 2008), face recognition (Andersson et al, 2008;Lajiness-O'Neill et al, 2005) and social skills (Baker & Vorstman, 2012;Baker & Skuse, 2005) have been consistently described in 22q11DS. Furthermore, functional connectivity alterations of high-level visual networks had already been identified in our former ICA study , and abnormal white matter structure in parietal regions have been described in DTI studies including both with increased (da Silva Alves et al, 2011;Simon et al, 2005Simon et al, , 2008 and decreased (Barnea-Goraly et al, 2003Sundram et al, 2010) fractional anisotropy.…”
Section: Reorganization Of Modular Communities In Patients With 22q11dsmentioning
confidence: 95%
“…For example, disruption of prepulse inhibition (PPI), a measure of sensorimotor gating and preattentive processes, is observed in both Df(16)A +/− mice (Stark et al, 2008) and individuals with 22q11.2 microdeletions(Ornitz et al, 1986; Sobin et al, 2005). In addition aspects of cognitive dysfunction in 22q11.2 microdeletion carriers(Casey et al, 1995) (Lajiness-O’Neill et al, 2005; Shprintzen et al, 1978) are also observed in Df(16)A +/− mice, as demonstrated by decreased accuracy in delayed non-match to place (DNMP) task of spatial working memory and deficits in both cued and contextual fear conditioning (Stark et al, 2008). Morphological analysis reveals that the CA1 neurons of Df(16)A +/− animals have simplified dendritic trees and decreased spine density (Mukai et al, 2008), which may partially account for reduction in hippocampal volume (Campbell et al, 2006; Eliez et al, 2000; Simon et al, 2005) in individuals with 22q11.2 microdeletions.…”
Section: Altered Mirna Expression and Function In Various Neuropsymentioning
confidence: 99%
“…Indeed, it has been suggested that short-term memory of unknown faces may be impaired in 22q11DS. In particular, when children with 22q11DS were asked to recognise faces that had been learned immediately before, they performed poorer not only compared with controls but also compared with their performance on other memory tasks (e.g., visual-spatial; Campbell 2006; Lajiness-O’Neill et al 2005). Furthermore, we recently reported that children with 22q11DS (a subgroup of those reported in the current paper) had a significantly reduced performance on face processing tests of gaze direction, identity and emotion recognition compared with intellectually, age- and gender-matched children with Williams syndrome (WS; Campbell et al 2009).…”
Section: Introductionmentioning
confidence: 99%